"Crossing the River by Feeling the Stones": How Borders, Energy Development and Ongoing Experimentation Shape the Dynamic Transformation of Yunnan Province. Issue 5 (20th October 2021) - Ptak, Thomas; Konrad, Victor
ABSTRACT: This article details the dynamic transformation of Yunnan's border regime during the early twenty-first century through the Great Western Development Strategy, Bridgehead and Belt and Road Initiative. Although China's macro-scale national strategies frame border change, experimental ideology and local-scale mechanisms drive border change and refine through constant adjustment. As illustrated in this article, border positioning and repositioning is incremental, constituted of many small and different components, dependent on locals and localities, and employing an array of border mediation strategies. Seemingly large scale border alteration is actually accrued through micro-changes, small scale experiments in specific places, trial and error adjustments and, essentially "crossing the river by feeling the stones." Whereas Yunnan's geostrategic location and vast energy resources have catapulted the province through rapid growth and into a globalized international context, ongoing transformation has also bolstered boundaries and bordering processes in Yunnan's mobile border regime and generated antithetical and reactionary bordering responses that need to be viewed within a post-globalization border framework.